Smart Safe Deposit Box Based on Internet of Things - Mohamad Abdul Wahid Romadhoni; Naufal Majdi; Purwidi Asri (Future Science, 2021)
The development of Internet of Things technology today is overgrowing in various fields, one of which is security. Safe-deposit box system is considered less safe because there is no warning to the owner. This study proposes a safe deposit box system that has a token security feature based on the internet of things. This system uses a webcam that functions to take pictures automatically. The image is sent to the server via the FTP protocol. It has two levels of users, namely admin, and guest. This system has a warning alarm, and notifications feature that works when the safe door is opened by force. Keyword: internet of things, safe deposit box